2018
DOI: 10.1155/2018/8073476
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Preterm Delivery: Proposal of a New Diagnostic Algorithm

Abstract: Predicting preterm delivery within 7 days is very important for the proper timing of glucocorticosteroid administration. If within 7 days after glucocorticosteroid administration, the delivery does not occur, it remains questionable if repeated glucocorticosteroid therapy results in improved infant respiratory function. Therefore, differentiation of preterm delivery from false preterm delivery is clinically significant. The aim of this study was to create a diagnostic algorithm to distinguish preterm delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
(41 reference statements)
2
12
1
Order By: Relevance
“…This is in accordance with a previous proteomic study using plasma from asymptomatic women at 17–28 weeks of gestation, in which IGFBP-2 was detected as a protein that distinguished cases of preterm birth from term controls [ 29 ]. We cannot explain the discrepancy between the present findings and those of earlier reports on preterm labor [ 26 , 27 ], but the clinical significance and mechanisms of action of IGFBP-2 identified in the present study require further confirmation in large cohort studies. Finally, in the current study, the plausible mechanisms by which increased plasma IGFBP-2 levels in cervical insufficiency contribute to SPTD (cerclage failure) may be related to abnormal placental function, leading to the activation of placental vascular insufficiency, a known significant risk factor associated with SPTD [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with a previous proteomic study using plasma from asymptomatic women at 17–28 weeks of gestation, in which IGFBP-2 was detected as a protein that distinguished cases of preterm birth from term controls [ 29 ]. We cannot explain the discrepancy between the present findings and those of earlier reports on preterm labor [ 26 , 27 ], but the clinical significance and mechanisms of action of IGFBP-2 identified in the present study require further confirmation in large cohort studies. Finally, in the current study, the plausible mechanisms by which increased plasma IGFBP-2 levels in cervical insufficiency contribute to SPTD (cerclage failure) may be related to abnormal placental function, leading to the activation of placental vascular insufficiency, a known significant risk factor associated with SPTD [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…IGFBP-2 is known to regulate the activity of insulin growth factor, which is involved in the control of placental and fetal growth and development [ 23 ] and is expressed in human fetal and placental tissues [ 24 , 25 ]. Previous studies have shown that serum IGFBP-2 levels are not significantly altered by preterm birth, whereas serum IGFBP-1 levels are significantly altered [ 26 , 27 ]. In contrast, our group previously reported that low plasma levels of IGFBP-2 were independently associated with histologic chorioamnionitis in women with preterm labor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it was also con rmed that IL-27 can up-regulate the expression of ICAM-1 in WISH cells. This was in consistent with a study of 622 pregnant women with threatened preterm birth, ICAM-1 was found to be signi cantly associated with PL [37]. Therefore, these results help us better understand the reason why Th1 cells accumulated at the maternal-fetal interface in PL.…”
Section: Discussionsupporting
confidence: 91%
“…Vaginal infection, chronic inflammation, and inflammation-associated conditions like obesity and hypertension place a pregnancy at risk [5][6][7]. In fact early-to mid-gestation markers of low grade systemic inflammation, including increased pro-inflammatory cytokines interleukin (IL)-6, IL-8 and c-reactive protein and decreased anti-inflammatory IL-10, have been detected in women experiencing sPTB [8][9][10][11]. Notably, body mass indices (BMIs) for obesity (>30 kg/m 2 ) and underweight (<18.5 kg/m 2 ) relative to the normal range increase risks of sPTB [12][13][14][15][16], and the association of BMI with inflammation also exhibits a "U-shaped" behavior [17].…”
Section: Introductionmentioning
confidence: 99%